Saphisme et décadence dans Paris fin-de-siècle - Albert, Nicole G. (La Martinière, 2005)
Figures emblématiques des années 1900, les saphistes sont associées aux premiers balbutiements d'un féminisme qui dérange et qui, par réaction, nourrit d'inépuisables fantasmes. Objets de scandale ou héroïnes, elles inspirent artistes et poètes. C'est l'ensemble de ces représentations ambiguës qui sont ici analysées.
Keywords: 1800-1899; approches et analyses; arts; corps; discipline; discours dominant; europe; france; lesbianisme; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; études littéraires

Reclaiming female agency: feminist art history after postmodernism - Broude, Norma..; Garrard, Mary D.; Broude, Norma; Garrard, Mary D. (University of California Press, 2005)
This volume is the third in an influential series of anthologies by editors Norma Broude and Mary D. Garrard that challenge art history from a feminist perspective. Following their Feminism and Art History: Questioning the Litany (1982) and The Expanding Discourse: Feminism and Art History (1992), this new volume identifies female agency as a central theme of recent feminist scholarship. Framed by a lucid and stimulating critical introduction, twenty-three essays on artists and issues from the Renaissance to the present, written in the 1990s and after, offer a nuanced critique of the poststructuralist premises of 1980s feminist art history.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; post-structuralisme; postmodernisme; premier cycle; périodes historiques; thématiques